Study on the storage changes of home-made butter square packed in paperboard box - Bueno, Gemma L. (1996.)
Home made butter squares were packed in a paperboard box and stored at ambient conditions.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Butter square; Papperboard box